Contribution of anthropogenic sulfate aerosols to the changing Euro‐Mediterranean climate since 1980. Issue 15 (4th August 2014) - Nabat, Pierre; Somot, Samuel; Mallet, Marc; Sanchez‐Lorenzo, Arturo; Wild, Martin
Abstract Since the 1980s anthropogenic aerosols have been considerably reduced in Europe and the Mediterranean area. This decrease is often considered as the likely cause of the brightening effect observed over the same period. This phenomenon is however hardly reproduced by global and regional climate models. Here we use an original approach based on reanalysis‐driven coupled regional climate system modeling to show that aerosol changes explain 81 ± 16% of the brightening and 23 ± 5% of the surface warming simulated for the period 1980–2012 over Europe. The direct aerosol effect is found to dominate in the magnitude of the simulated brightening. The comparison between regional simulations and homogenized ground‐based observations reveals that observed surface solar radiation and land and sea surface temperature spatiotemporal variations over the Euro‐Mediterranean region are only reproduced when simulations include the realistic aerosol variations.